Komparasi Antraksi 3 Destinasi Wisata Di Malang - Dewi, Dinda Citra; Arshintawaty, Sherly Gracia; Juniati, Iis; Romadhan, Mohammad Insan (CV. ITTC INDONESIA, 2025)
Malang City is one of the tourism cities in East Java that has various interesting destinations, both traditional, modern, and public open spaces. This study aims to compare tourist attractions from three locations with different characters but equally popular, namely Malang Square, Klojen Market, and Cafe CR Malang. The study was conducted using a qualitative descriptive method through direct observation, short interviews with visitors, and literature studies. The results of the study show that the three destinations have their own uniqueness that adapts to different visitor segments. Malang Square is a family-friendly open public space, Klojen Market emphasizes local economic and cultural aspects, while Cafe CR Malang presents a modern and aesthetic nuance that attracts the younger generation. This comparison shows the importance of the diversity of tourist destinations in the development of sustainable urban tourism.